Continuing Professional Development and English Language Teachers’ ICT Uptake - Alivi, Justsinta Sindi; Norahmi, Maida; Mardiana, Wiwik (General English Education, 2024)
This paper presents the discussion on the impact of Continuing Professional Development (CPD) to English language teachers’ decision and performance in the use of Information and Communication Technology (ICT) in teaching. This study carried out a multiple study on two different teachers from different institutional and academic status background in Indonesia. Interviews were carried out to the participant to obtain deeper information concerning their experience in different types of CPD, and how it could influence the way they perceive ICT usefulness and enhance their teaching performance. The result of this study is expected to provide practical contributions particularly to the policy makers to improve teachers’ competences by designing appropriate curriculum and CPD in accordance with the teachers’ need in the digital era. The result of study indicated that both teachers tended to develop their TPACK (Technological, Pedagogical and Content Knowledge) competences from informal CPD they had from informal co-learning with colleagues and informal network learning from online resources. They also pointed out that governments provided teachers with online-based training that they could access to governments’ official websites.